The impact of the purposes of Sharia on the fatwas of the Supreme Council for Issuing Fatwas in the Kurdistan Region - Abdullah Saeed Waise (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This research deals with the statement of the impact of the purposes of Sharia on the fatwas of the Supreme Council for Fatwa in the Kurdistan Region, with the aim of highlighting the position of scholars in general and the Supreme Council for Fatwa in Kurdistan in particular, and clarifying its great role in it and its effective role in resolving inquiries, and there is a great reception by Muslims in the region on Fatwas issued by them, and research proves that what was issued by them is fully consistent with the purposes of Islamic law.